(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: During pregnancy, there are many superstitions throughout the world, especially in the developing countries like Bangladesh. Objective: This study was aimed to know the status of superstitions related to pregnancy among people. Methodology: This descriptive type of cross-sectional study was conducted in the outpatient of department in Combined Military Hospital, Dhaka, Bangladesh from January 2018 to March 2018 for a period of three months. Total 96 persons were recruited after taking verbal consent. Result: Among the study group having at least one superstition was in 69.8% of total participants showing in figure 1. In 25 to 40 years of age group the superstitions were more common and it was 85.0% showing in table1. On the educational background, illiterate group having more superstitions 81.13%, primary education group 65.21%, SSC 50% and above SSC 33.33% showing in table 3. On the basis of gender, male (58.233%) and Female (71.42%) were superstitious in at least one superstition. On the basis of socioeconomic status, lower class 92.72%, lower middle class 54.54% and middle class 21.05% were superstitious in at least one superstition. On the basis of occupation, housewives (89.90%), students (16,66%), service holder(30%) and farmer(50%) having at least one superstitious. On the basis of religion; the superstitious individuals were Muslim 59%, Hindu 97%, and others 67.16%. Conclusion: Superstitions related to pregnancy are very common in Bangladesh. Superstitious are more related to illiteracy, low socioeconomic condition and with house wives who remain inside. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 172-176